Does Government Agricultural Machinery Assistance Increase Paddy Yield? Impact Evaluation in West Java Province Using Propensity Score Matching - Ruslan, Kadir; Sukma, Weni Lidya (Jurnal Ekonomi Dan Statistik Indonesia, 2025)
Amidst a decade of increasing government agricultural machinery assistance, paddy yield in East Java, a major paddy-producing region in Indonesia, has stagnated, threatening the region's food security. This study evaluates the impact of such assistance on paddy yield. Using Propensity Score Matching (PSM) and Endogenous Switching Regression (ESR) on 2018 and 2021 National Cro-cutting Survey data, we found that, on average, government agricultural machinery assistance significantly increased paddy yield by 0.66 to 0.68 tons per hectare. However, the impact was greater in 2018 (0.9 tons per hectare) than in 2021 (0.14 tons per hectare), with the latter not statistically significant, likely due to the pandemic and the broader adoption of mechanization. OLS regression analysis further suggests that yield gains only occur when assistance aligns with farmers' needs. Our findings underscore the importance of a farmer-centric approach and strengthening farmer institutions to effectively manage the machinery assistance. Expanding mechanization to farmers who have not yet adopted it is also recommended.